Wave energy absorption of a wave farm with an array of buoys and flexible runway. (15th August 2016) - Zhang, H.C.; Xu, D.L.; Liu, C.R.; Wu, Y.S.
Abstract: A novel wave energy extraction method, based on the PTO (Power Take-Off) mechanism, is developed by utilizing an array of buoys connected with a flexible runway. Hydrodynamic interactions among the buoys are analyzed using an exact algebraic method based on linear wave theory in the frequency domain. A parametric governing equation of compounded wave energy converter referred to as a wave farm is formulated by using Hamilton's principle which can be discretized by using Galerkin method. The effects of wave condition and the parameters of PTO on the wave energy absorption and displacement of runway are analyzed. The results show that the energy extraction and displacement of the runway can reach an optimal balance by optimizing the stiffness of connectors and damping coefficient of PTO which leads to the benefits of more efficient energy absorption and less movement of the runway simultaneously. The quality of the wave farm is examined by introducing the q -factor to understand the effect of the array configuration. This research work is aimed to provide a theoretical guideline for wave energy converter design. Highlights: A wave energy converter of multiple buoys supporting a flexible runway is developed. The system has functions of wave energy extraction and ocean space utilization. An exact parametric model of wave farm is formulated based on linear wave theory. The energy extraction and stability of the runway can reach an optimal balance.